A Note on a Broken-Cycle Theorem for Hypergraphs - Trinks Martin (Discussiones Mathematicae Graph Theory, 2014)
Whitney’s Broken-cycle Theorem states the chromatic polynomial of a graph as a sum over special edge subsets. We give a definition of cycles in hypergraphs that preserves the statement of the theorem there